Immersive virtual reality experience: Showcasing wadai Banjar traditional cake with hand gesture controls - Tolle, Herman; Zakiah, Siti; Huda, Fais Al (Bulletin of Social Informatics Theory and Application, 2024)
Virtual reality (VR) has revolutionized the way we engage with digital content, offering immersive environments that combine education and entertainment. This study explores the innovative application of VR to introduce Wadai Banjar, traditional cakes from the Banjar tribe in Indonesia, through a virtual environment enhanced by hand gesture interaction. Using hand-tracking technology on the Meta Quest 2 headset, users can interactively explore the making and cultural history of Wadai Banjar in a highly engaging and immersive manner. The study employs the Game Development Life Cycle (GDLC) methodology. It evaluates the experience through Playtesting, Gameflow, and assessments of telepresence, controller naturalness, and cybersickness. The findings reveal high levels of immersion, with a telepresence score of 64.46/70, controller naturalness of 62.3/70, and low cybersickness at 16/70. These results highlight VR's potential as a cultural education platform to preserve intangible heritage, particularly in engaging younger generations with the rich traditions of Indonesian cuisine. This research paves the way for future efforts to preserve cultural heritage through interactive technologies.